2006
DOI: 10.1161/01.atv.0000195791.83380.4c
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Macrophage Arginase I as a New Candidate Gene of Atherosclerosis Resistance

Abstract: Objective-Our laboratory has previously created 2 strains of rabbits with genetically determined high-atherosclerotic response (HAR) and low-atherosclerotic response (LAR). The aim of the present study was to identify new genes of atherosclerosis susceptibility in macrophages from the 2 strains. Methods and Results-Suppression subtractive hybridization was used to screen for genes with higher expression in macrophages from LAR rabbits. We identified a cDNA fragment with high homology to human arginase I (AI; 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 33 publications
(34 reference statements)
2
32
0
2
Order By: Relevance
“…In a study done to identify new genes of atherosclerosis susceptibility in macrophages from the two strains of rabbits with genetically determined high-atherosclerotic response (HAR) and low-atherosclerotic response (LAR), it was found that high expression of arginase I in macrophages may contribute to atherosclerosis resistance of LAR rabbits, possibly by conferring anti-inflammatory effects in the vessel wall. 521 This observation goes well with an earlier study where it was shown that arginase-1 was one of the 11 downregulated genes in macrophage foam cells. 223 In a study done to investigate the associations of the MnSOD polymorphism (valine-to-alanine) with its activity in leukocytes, macrophage apoptosis induced by Ox-LDL and CAD, it was found that the alanine allele in the signal peptide of MnSOD increases its mitochondrial activity and protects macrophages against the Ox-LDL-induced apoptosis, thereby reducing the risk of CAD.…”
Section: M a C R O P H A G E S A N D P O L Y M O R P H I S Msupporting
confidence: 88%
“…In a study done to identify new genes of atherosclerosis susceptibility in macrophages from the two strains of rabbits with genetically determined high-atherosclerotic response (HAR) and low-atherosclerotic response (LAR), it was found that high expression of arginase I in macrophages may contribute to atherosclerosis resistance of LAR rabbits, possibly by conferring anti-inflammatory effects in the vessel wall. 521 This observation goes well with an earlier study where it was shown that arginase-1 was one of the 11 downregulated genes in macrophage foam cells. 223 In a study done to investigate the associations of the MnSOD polymorphism (valine-to-alanine) with its activity in leukocytes, macrophage apoptosis induced by Ox-LDL and CAD, it was found that the alanine allele in the signal peptide of MnSOD increases its mitochondrial activity and protects macrophages against the Ox-LDL-induced apoptosis, thereby reducing the risk of CAD.…”
Section: M a C R O P H A G E S A N D P O L Y M O R P H I S Msupporting
confidence: 88%
“…20 Although Arg I could be a new candidate gene of atherosclerosis resistance, 21 no reports exist of the effects of Arg I in these diseases. As well, the fundamental mechanism still remains unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…Arg1 variant with increased activity in cholesterol-fed rabbits 241% Arg1 (arginase 1) variant in atherosclerosis resistant rabbits was shown to have greater activity (1775,1785). Arg1 is greatly increased in regressing plaques and produces polyamines which promote resolution of inflammation and reduces iNOS production of NO in macrophages.…”
Section: Arg1mentioning
confidence: 99%